Preparative SDS-PAGE Electroelution for Rapid Purification of Alkyl Hydroperoxide Reductase from Helicobacter pylori - T Mohammadian; M Doosti; M Paknejad; F Siavoshi; S Massarrat (Tehran University of Medical Sciences, 2010)
"nBackground: Alkyl hydroperoxide reductase (AhpC) of Helicobacter pylori is considered as a diagnostic antigen. Therefore, this antigen can be used to detect H. pylori infection by stool immunoassays such as ELISA. The aim of this study was to simplify the AhpC protein purification procedures."nMethods: For whole cell protein extraction, the bacterial cells were ruptured by octly-β-D glucopyranoside. The isolation and purification of  AhpC protein were attempted by various techniques including ammonium sulfate precipitation, dialysis, preparative sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and electroelution."nResults:A simple method was used for protein purification AhpC protein. One-dimensional preparative gel electrophoresis allows a single and short purification step; the high resolution capacity of this technique leads to a high level of purity of the protein. Moreover, it avoids contamination by other non-specific proteins which often appear during protein purification by column chromatography."nConclusion: The present method is simple, rapid and makes it possible to preparate AhpC from H. pylori